Factors influencing economic wellbeing by Resettlement in urban market redevelopment: exploring the Kejetia project in Ghana - Francis Mensah; Guoqing Shi; Yu Qingnian (Urban, Planning and Transport Research)
Urban market redevelopment has become the catalyst to re-invent space and alleviate poverty by local governments, yet, it poses economic wellbeing concerns, particularly for the resettled traders. The present study seeks to examine the factors influencing the economic wellbeing of the affected traders, using the Kejetia project in Ghana as a case study. The study responded to two questions: what are the factors, and how do the factors affect each other? A proposed model was developed and hypotheses were initiated. A quantitative methodology was used to elicit and analyse data using SmartPLS 4.0. A purposive sampling technique was used to select 240 respondents from the drivers and sellers’ groups. The measurement model tested reliable and valid. The findings listed deprivation, economic security, income, consumption, and wealth as the reliable factors. These factors were determined by certain economic indicators. The hypotheses were significant and supported. Its findings implied that the factors directly impacted others. The study concludes that resettlement in the Kejetia project triggered complex economic issues for affected traders, particularly drivers. The key implication of the findings is to inform policy that the economic wellbeing of drivers and sellers is better improved if the impeding factors and indicators are well-managed.